2020
DOI: 10.1007/s11116-020-10147-3
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting the service? Understanding the factors affecting bus ridership over time at the route level in Montréal, Canada

Abstract: Like many cities across North America, Montréal has experienced shrinking bus ridership over recent years. Most literature has focused on the broader causes for ridership decline at the metropolitan or city level; few have considered ridership at the route level, particularly while accounting for various operational attributes and accessibility-to-jobs issues. Because service adjustments take place-and are felt by riders-at the route level, it is essential to explore busridership phenomena at this same scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 33 publications
2
22
0
3
Order By: Relevance
“… Tang and Thakuriah (2012) and Brakewood et al (2015) use fixed-effects models at the route level to evaluate the impact of real-time passenger information on ridership. More recently Diab et al (2020) modeled the impact of service attributes on ridership between 2012 and 2017 in Montreal, QC. They find a positive correlation with vehicle speed, number of stops, job accessibility, and several measures of service quantity, including frequency, a dummy variable for routes with headways less than 10 min, and a dummy variable for the express network.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Tang and Thakuriah (2012) and Brakewood et al (2015) use fixed-effects models at the route level to evaluate the impact of real-time passenger information on ridership. More recently Diab et al (2020) modeled the impact of service attributes on ridership between 2012 and 2017 in Montreal, QC. They find a positive correlation with vehicle speed, number of stops, job accessibility, and several measures of service quantity, including frequency, a dummy variable for routes with headways less than 10 min, and a dummy variable for the express network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Overall, trip-generation propensities of both modes show a decline but is not statistically significant for the automobile trip-making propensity. This finding is in line with what has been reported for other regions (Diab, Deweese, et al, 2020;Diab, Kasraian, et al, 2020;Miller et al, 2018). There is a decreasing trend in transit usage among the younger populations as it is found that they are more reluctant to generate trips if they can fulfil their activities without physically leaving their place of residence (Alemi et al, 2019;Circella et al, 2016;Enam & Konduri, 2018;Olsson et al, 2020).…”
Section: Marginal Effects and Policy Implicationssupporting
confidence: 93%
“…While some research relates accessibility to various outcomes, such research needs to be developed further to provide stronger evidence on the impacts of improving accessibility. In our previous research with colleagues, we have shown that improving accessibility by public transport in a region will lead to increase in public transport use at various scales (stop, route, census tract and system levels) (Cui, Boisjoly, Miranda-Moreno, & El-Geneidy, 2020;Diab, DeWeese, Chaloux, & El-Geneidy, 2020;Owen & Levinson, 2015;Wu, Levinson, & Owen, 2021b).…”
Section: Making Accessibility Work In Practicementioning
confidence: 98%